LO54: The CanadiEM Junior Editor program: a quantitative study and program evaluation. (May 2019) - Wakeling, S.; Chan, T.; Thoma, B.
Abstract : Introduction : CanadiEM.org is a multi-author open access medical education website which aims to improve emergency care in Canada by building an online community of practice for healthcare practitioners and providing them with high quality, freely available educational resources. It is used by physicians, allied health professionals, and trainees globally. Junior (medical student and/or resident) Editors are key members of the community who are mentored to advance their academic skills and knowledge for their careers and the healthcare field. The program also aims to increase the sustainability of the CanadiEM project by supporting the creation and publishing of online content. We aimed to assess the impact and efficacy of this program while discovering ways to improve it.Methods : The experience of all current and previous Junior Editors were assessed through a survey developed by the authorship team for this purpose. The survey consisted of 48 questions, including 15 multiple choice questions rated using a Likert Scale, 10 open-ended questions, and 23 demographic or binary yes/no questions. The participants' perceptions of their experience, desire for future involvement, and opinions regarding implementation of the program at other medical education websites were assessed using open-ended qualitative questions. These responses were thematically analyzed.Results : A total of 28 Junior Editors responded (71.7% of those surveyed). They listed their responsibilities as uploading/copyediting posts, authorship of posts, infographic creation, social media promotion, authorship of podcast summaries, editing of podcasts, and logo design. Results revealed a positive experience across all domains, with participants citing a better experience when compared to previous similar roles. 85.7% (24/28) stated they achieved their expectations from the program, and 82.1% (23/28) would incorporate this program into another medical education website if given the opportunity.Conclusion : Junior Editors reported positive experiences across all responsibilities, with particular value placed on digital and authorship skills development, inspiration for future FOAMed, research engagement, and mentorship/networking. Through collaboration with current team members, we will implement improvement initiatives. Based upon these results, we believe that the Junior Editor model may also be viable within other medical education communities.